A sociodental approach to assessing dental needs of children: concept and models - S. GHERUNPONG, G. TSAKOS & A. SHEIHAM (Paediatric Dentistry, 2006)
Assessing dental needs is the basis of planning dental services and treatment. Appropriately assessed population needs improve estimates of resources, rational allocation of dental services, and efficient dental care expenditure.